Key Internet of Things Technology and Application Research - Xu Bing (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Key core technologies of IOT (internet of things) have to be addressed to achieve rapid development. This paper focused on studying RFID, wireless sensor network (WSN) and TCCP which were integrated to address the IOT application problems. Meanwhile, an IOT architectural model was established and the IOT applications in real-time medical monitoring, intelligent transportation system (ITS), intelligent appliances and intelligent agriculture were introduced.